This website uses cookies to ensure you get the best experience. Learn more

yc

yc Sentence Examples

  • +X) happens to be zero, X lies at infinity in a determinate direction; unless - aA is the barycentre of (3B, yC, ...

    0
    0
  • yc,o f30vX1 7), named after the hill, is to be compared in origin and fundamental character with the council of chiefs or elders which we find among the earliest Germans, Celts, Romans, and other primitive peoples.

    0
    0
  • Also since dx has been stretched to +dy p&,(dx +dy) =po&odx or p&'(I +dy/dx) = (29) Substituting from (28) in (27) Y&a + P(2)U 2 (I + dy (3) 2 = p oc?oU 2, 0) and substituting from (29) in (30) Y&ao dx + pocZoU 2 + dx) = p owoU 2, (31) whence Yc = powoU2, or U2 = Y/ p, (32) where now p is the normal density of the rod.

    0
    0
  • () VC1 v.4 t i ITN1-1"t'eC .1C* A t i[rt C :YC)Y(:1 V 5 1 t t 7.C)Y 1'71t?C,'1'J.?.A.

    0
    0
  • +X) happens to be zero, X lies at infinity in a determinate direction; unless - aA is the barycentre of (3B, yC, ...

    0
    0
  • yc,o f30vX1 7), named after the hill, is to be compared in origin and fundamental character with the council of chiefs or elders which we find among the earliest Germans, Celts, Romans, and other primitive peoples.

    0
    0
  • Also since dx has been stretched to +dy p&,(dx +dy) =po&odx or p&'(I +dy/dx) = (29) Substituting from (28) in (27) Y&a + P(2)U 2 (I + dy (3) 2 = p oc?oU 2, 0) and substituting from (29) in (30) Y&ao dx + pocZoU 2 + dx) = p owoU 2, (31) whence Yc = powoU2, or U2 = Y/ p, (32) where now p is the normal density of the rod.

    0
    0
  • () VC1 v.4 t i ITN1-1"t'eC .1C* A t i[rt C :YC)Y(:1 V 5 1 t t 7.C)Y 1'71t?C,'1'J.?.A.

    0
    0
Browse other sentences examples →